MATS deepfreeze airlift (United States Air Force, 1961)
Documents the Military Air Transport Service airlift conducted in the fall of 1960 in support of an antarctic scientific expedition. This film has been digitized because it has a high level of Vinegar Syndrome (chemical deterioration). That condition will prevent any captured images from being 100% perfect. Our goal is to present the content of the film in a digital format that is as good and the least distracting as possible.